Reviving Palmyra in Multiple Dimensions - Silver, Minna (Whittles, 2018)
A classic example of digital archaeology and virtual reconstruction; Provides a comprehensive and fascinating study of Palmyra, lifting it from the ruins; A beacon for the recording of international cultural heritage.